Strategi Pemasaran Restoran Cucina dalam Meningkatkan Daya Saing di Industri Hospitality Premium - Ni Putu Ari Aira Jasmin; Ni Putu Bayu Widhi Antari; Putu Dyah Permatha Korry; I Nyoman Gede Arya Diatmika (Economic Reviews Journal, 2026)
The development of the tourism industry in Bali has significantly contributed to the growth of the hospitality sector, particularly restaurants located in star-rated hotels. This situation has increased competition among restaurants in attracting both international tourists and local customers. Cucina Restaurant, located at Sofitel Bali Nusa Dua Beach Resort, is a fine dining restaurant that offers authentic Italian cuisine combined with premium service standards. In order to face the growing competition, restaurants need to implement effective marketing strategies to maintain their existence and improve their competitiveness in the premium hospitality industry. This study aims to analyze the marketing strategies implemented by the management of Cucina Restaurant in improving the restaurant’s competitiveness. This research uses a qualitative method with a descriptive approach. Data collection techniques include observation, interviews with management staff involved in operational and marketing activities, and documentation related to the restaurant’s marketing efforts. The collected data were analyzed using the marketing mix concept which includes product, price, place, promotion, people, process, and physical evidence. The results show that the marketing strategies implemented by Cucina Restaurant include developing high-quality food products with an authentic Italian concept, setting prices that align with the premium market segment, utilizing its strategic location in the Nusa Dua tourism area, and conducting promotional activities through social media, collaborations with influencers, and various culinary events. In addition, service quality, professional human resources, and an elegant restaurant atmosphere play an important role in creating a memorable dining experience for customers. Through the implementation of these marketing strategies, Cucina Restaurant is able to enhance its competitiveness within the premium hospitality industry.